2018
DOI: 10.1007/s00122-018-3105-7
|View full text |Cite
|
Sign up to set email alerts
|

CsMYB36 is involved in the formation of yellow green peel in cucumber (Cucumis sativus L.)

Abstract: A yellow green peel mutant (ygp) in cucumber was caused by a mutation in Csa2G352940 encoding MYB36 transcription factor. Peel color is one of the important agronomic traits of cucumber (Cucumis sativus L.). However, studies on the molecular regulation mechanism of peel color in cucumber are few. In this study, a cucumber yellow green peel mutant (ygp) of cucumber mutagenized with ethylmethylsulfone by using a wild type cucumber with dark green peel was identified. Pigment measurements indicated that the chlor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 53 publications
0
33
0
Order By: Relevance
“…Because there are many secondary metabolites in the peel, such as pigments, tannins and aromatic compounds, the peel can show a variety of colors [ 6 , 7 ]. Peel color is an important standard of food cucumber quality traits, which can greatly affect consumers’ choices, so it has an important commodity value [ 8 ]. The commodity value of cucumber peel color has strong regional characteristics, so consumers in different regions have different preferences for it, and it is impossible to use a unified standard to judge the quality of a certain peel color.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because there are many secondary metabolites in the peel, such as pigments, tannins and aromatic compounds, the peel can show a variety of colors [ 6 , 7 ]. Peel color is an important standard of food cucumber quality traits, which can greatly affect consumers’ choices, so it has an important commodity value [ 8 ]. The commodity value of cucumber peel color has strong regional characteristics, so consumers in different regions have different preferences for it, and it is impossible to use a unified standard to judge the quality of a certain peel color.…”
Section: Introductionmentioning
confidence: 99%
“…The peel color is a quantitative character, and its gene expression is affected by the environment [ 8 ]. Hutchins first classified the peel color of mature cucumber fruit into four categories: red, orange, yellow and cream, and proposed it was controlled by two genes R and C [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…KASP is a flexible, cost-effective tool to distinguish alleles between parents and progeny in segregating populations. KASP has been used to verify causal genes in cloned regions of cucumber (Cucumis sativus L.) 31,36 . Our genotyping analysis showed that SNP 25,986,068 of BraA03g050600.3C cosegregated with the phenotype of the F 2 segregation population.…”
Section: Discussionmentioning
confidence: 99%
“…Sakuraba et al 30 proposed that SGRs recruit CCEs based on their ability to bind light-harvesting complex II (LHCII) and their interactions with CCEs. Shimoda et al (2016) showed that SGRs encode mg-dechelatases 31 . STAY-GREEN is a functional mg-dechelatase that extracts magnesium from free chlorophyll and chlorophyll complexes and therefore participates in chlorophyll and photosystem degradation.…”
Section: Introductionmentioning
confidence: 99%
“…In cucumber, two genes responsible for fruit color were identified by map-based cloning. A single-nucleotide insertion in APRR2 was responsible for a white immature fruit color (Liu H. et al, 2016), while a mutation in MYB36 resulted in the formation of a yellow-green peel mutant (Hao et al, 2018). A 4-bp insertion in a putative R3 MYB repressor, SIMYBATV , led to anthocyanin accumulation in tomato fruit (Cao et al, 2017).…”
Section: Introductionmentioning
confidence: 99%